2021
DOI: 10.1002/adma.202103881
|View full text |Cite
|
Sign up to set email alerts
|

A Pyrite Iron Disulfide Cathode with a Copper Current Collector for High‐Energy Reversible Magnesium‐Ion Storage

Abstract: Owing to its low cost, high theoretical capacity, and environmentally friendly characteristics, pyrite FeS2 demonstrates promise as a cathode material for high‐energy metal‐anode‐based rechargeable batteries. When it is used in a rechargeable magnesium battery (RMB), the electrode couple exhibits an extremely low theoretical volume change upon full discharge. However, its electrochemical Mg‐ion storage is considerably hindered by slow reaction kinetics. In this study, a high‐performance FeS2 cathode for RMBs u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 81 publications
3
30
0
Order By: Relevance
“…Cu is widely used in Mg–S batteries in the form of current collector or interlayer. , Because of the chemical interaction between Cu and S, the shuttle effect could be inhibited effectively . It is reported that the Cu current collector could be involved in the electrochemical reactions, enabling the transition of active materials and realizing the stability of the battery system . In this work, the effect of current collectors is investigated.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cu is widely used in Mg–S batteries in the form of current collector or interlayer. , Because of the chemical interaction between Cu and S, the shuttle effect could be inhibited effectively . It is reported that the Cu current collector could be involved in the electrochemical reactions, enabling the transition of active materials and realizing the stability of the battery system . In this work, the effect of current collectors is investigated.…”
Section: Results and Discussionmentioning
confidence: 99%
“…46 It is reported that the Cu current collector could be involved in the electrochemical reactions, enabling the transition of active materials and realizing the stability of the battery system. 47 In this work, the effect of current collectors is investigated. When employing aluminum foil-coated carbon as the current collector, the S 0.96 Se 0.04 @CMK3 cathode delivers low capacity and poor cycling performance in Figure S8 and the overcharging results from the severe shuttle effect.…”
Section: Resultsmentioning
confidence: 99%
“…As activation progresses, the electrolyte slowly penetrates the cathode and the wettability gradually increases, thus more cathode materials participate in the oxidation reaction. [7,24,25] The discharge capacity in the first cycle was ≈167 mAh g −1 , and did not show a voltage plateau. The voltage polarization was large in the first few cycles but decreased as the cycles increased.…”
Section: Electrochemical Performance Of Ncse@tivc Heterostructurementioning
confidence: 99%
“…S and Se, which possess multiple oxidation states, show weak Coulomb attraction to Mg by forming Mg-S or Mg-Se bonds that promote rapid magnesium ion reaction kinetics. [6] Therefore, transition metal chalcogenides such as CuS, [5] FeS 2 , [7] VS 2 , [8] NiCo 2 Se 4 , [9] and Ni 3 Se 4 [10] are considered promising as MIB hosts and are appropriate cathode materials for magnesium ion storage. Further investigation of high-performance cathode materials based on optimal structural design is an effective strategy in developing rechargeable magnesium batteries (RMBs).…”
Section: Introductionmentioning
confidence: 99%
“…[139] By controlling the intercalation chemistry using the Mg 2+ /Li + hybrid ion electrolyte, the battery exhibited a discharge capacity of 105 mAh g −1 at 10C and ultrafast diffusion kinetics with a high capacity retention of 93.6% at 20C and 87.5% at 30C. After the successful employment of Mo 6 S 8 cathode, transition metal dichalcogenides (TMDs) such as MoS 2 , [140] TiS 2 , [141] and FeS 2 [58] were also tried for MLHIBs with higher capacities (170-250 mAh g −1 ).…”
Section: Mg 2+ /Li + Hybrid Ion Batteriesmentioning
confidence: 99%